Chondroitin: a natural biomarker with immense biomedical applications. Issue 48 (6th September 2019) - Pal, Dilipkumar; Saha, Supriyo
Abstract : Naturally extracted glycosaminoglycan chondroitin sulphate is the reactive product of N -acetylgalactosamine andd -glucuronic acid. Abstract : Naturally extracted glycosaminoglycan chondroitin sulphate is the reactive product of N -acetylgalactosamine andd -glucuronic acid. Chondroitin sulfate (CS) extracted from Scophthalmus maximus, H. scabra, E. fraudatrix, M. magnum, and H. mexicana has shown remarkable anticoagulant, articular cartilage repair, corneal lesion healing, antidiabetic, and antiproliferative effects. Also, platinum and strontium nanoparticles of chondroitin sulfate are effective in osteoarthritis and exert anti-HSV2 and anti-angiogenic properties. A combination of chondroitin sulfate and RNA lipolexes demonstrates gene silencing effects in liver fibrosis. Chondroitin sulfate has also been used as a carrier for loxoprofen hydrogel preparation. Oligosaccharides of chondroitin sulfate showed effective inhibition of bovine testicular hyaluronidase enzyme as an antibacterial agent during pregnancy. Monoclonal antibody-recognized chondroitin sulfate A was effectively used to treat ameloblastoma. Selenium-chondroitin sulfate nanoparticles demonstrated positive effects in therapy of Kashin–Beck disease (KBD) and osteoarthritis.